Broke, USA : from pawnshops to Poverty, Inc. : how the working poor became big business - Rivlin, Gary (Harper Business, 2010)
"A unique and riveting exploration of one of America's largest and fastest-growing industries-- the business of poverty"--Provided by publisher.